Hospital Performance Efficiency And Bed Use Using Pabon Lasso Graphics In Nusa Tenggara Province Hospital West Before And During The Covid-19 Pandemic - Setya Oktariana; Kosasih, Kosasih; Rahadian Malik (Sean Institute, 2024)
Evaluating the performance of hospitals and the bed use using the efficiency indicators of hospitals can help and properly improve an accurate understanding of the set plans. This study aimed to identify factors and compare the performance efficiency towards the use of beds at West Nusa Tenggara Provincial Public Hospital, by employing the Pabon Lasso model before and during the Covid-19 pandemic in West Nusa Tenggara. This study is categorized as descriptive study using the qualitative approach in which the data were collected retrospectively from 2018 to 2022. There were three main indicators, namely bed occupancy rate, bed turnover rate, and the average length of stay. The excel software and Pabon Lasso model were used for data analysis. This research concludes that hospital performance and use of hospital beds were inefficient when the Covid-19 pandemic broke out compared to before the pandemic. Every effort should be made to identify and correct the factors contributing to poor efficiency conditions during the year. This analysis can be a guide for planning to increase hospital efficiency and disaster preparedness in the event of a third wave of Covid-19 or other possible pandemics.